A companion to contemporary art in a global framework - Davidson, Jane Chin; Jones, Amelia (Hoboken, NJ : Wiley-Blackwell, 2024)
"A Companion to Contemporary Art in a Global Framework (CAGF) is designed to provide a cultural, political, social, and aesthetic history of post-1980 visual arts in a global framework. The book is intended for students and specialists, but also for any reader interested in what art is and what it does in and beyond the Euro-American (shorthand for European and North American-so called Western) context. By "global framework," the book points to the necessity of moving beyond the Euro-American canons of art and artists while recognizing the structurally European bases for what we call art and its institutions. That is, the book does not claim global coverage, but rather offers a wide range of perspectives by curators, artists, art historians, performance studies scholars, and others on art since 1980 both within and beyond the Western context"--
I Live in the Fourth Dimension When I Create Landscapes / Senga Nengudi, artist statement -- Envisioning a More Just Future: Feminist Activist Art, Climate Change, and the Anthropocene / Lisa Bloom -- Ghosts in the Archive: Exorcism, Resurrection and the Possibilities of Repair / Hammad Nasar.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Art, Modern -- 20th century; Art, Modern -- 21st century; Art and society -- History -- 20th century; Art and society -- History -- 21st century